2023
DOI: 10.3390/app132212508
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Subsurface Thermal Characteristics for Green Parks

Muawia Dafalla,
Ahmed Al-Mahbashi

Abstract: The ground surface of green parks in arid and semi-arid areas may not be comfortable at specific times during the day and night due to the sun and the rate at which the subsoil gains or loses heat. Knowledge of the subsurface soil’s thermal properties can provide designers with convenient and comfortable settings. Design focus is generally directed toward stability, density, and hydraulic conductivity. An assessment of the thermal properties of clay–sand mixtures of 10%, 20%, and 30% clay content is conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Using the interrelationships between the thermal factors, several control rules for building thermal systems are developed from regression models to find new optimized rules or structures that improve performance. Several studies have shown the possibility of a model that improves efficiency for both thermal comfort and energy use, despite such precise control, and there are many studies that test a model's performance in actual buildings [14,15]. In addition, some studies dealing with various factors of occupant behavior by using simulation scenarios have been confirmed.…”
Section: Thermal Controls In Buildingsmentioning
confidence: 99%
“…Using the interrelationships between the thermal factors, several control rules for building thermal systems are developed from regression models to find new optimized rules or structures that improve performance. Several studies have shown the possibility of a model that improves efficiency for both thermal comfort and energy use, despite such precise control, and there are many studies that test a model's performance in actual buildings [14,15]. In addition, some studies dealing with various factors of occupant behavior by using simulation scenarios have been confirmed.…”
Section: Thermal Controls In Buildingsmentioning
confidence: 99%